Aquaculture Health Management : Design and Operation Approaches - Kibenge, Frederick S. B.; Powell, Mark D. (Elsevier Academic Press, 2020)
Aquaculture Health Management: Design and Operation Approaches is an essential reference for the diverse aquaculture community. With the steadily increasing importance of healthy fish production and the expansion of the animal aquaculture industry to new geographic areas, new microbial and parasitic species with pathogenic potential continue to emerge. The book covers the broad spectrum of fish and shellfish health, the functional roles of pathogen emergence, and the impacts of nutrition and preventative medicine such as pre- and probiotics, as well as chemical treatments, relevant legislation and more. This reference takes a comprehensive approach to understanding overall fish health management, making it valuable to aquaculturists, practitioners in aquatic animal health, veterinarians and all those in industry, government or academia who are interested in aquaculture and fisheries and their sustainable futures.